Professional nurses' attitudes towards providing termination of pregnancy services in a tertiary hospital in the North West province of South Africa - NE Mokgethi; VJ Ehlers; MM van der Merwe (AOSIS, 2006)
The Choice on Termination of Pregnancy Act (no 92 of 1996) was implemented during 1997. This study attempted to investigate professional nurses' attitudes towards rendering termination of pregnancy (TOP) services at a tertiary hospital in the North West Province of South Africa. A quantitative descriptive research design was used to study professional nurses' attitudes towards providing TOP services. The research results, obtained from questionnaires completed by professional nurses, indicated that most professional nurses' attitudes included that women should be at least 16 years of age to access these services; women should not be able to access repeated TOPs; nurses would prefer to administer pills rather than to use vacuum aspirations; nurses should work in TOP services by choice only. TOP centers should have better equipment, more resources and more staff members. Nurses working in TOP services would appreciate receiving more support from their families, friends, managers and communities. Some professional nurses experienced guilt, depression, anxiety and religious conflicts as a result of providing TOP services. Despite the legalisation of TOPs, these services remained stigmatised. Professional nurses did not want to work in these services and also did not want to be associated with them.